Strategic Teaching Thai Language in the 21st Century of Develop Analysis Thinking Skills - Klangburum, Charungphorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
This article aims to develop learners of critical thinking skills Performance in the 21st Century of students include Performance of Thinking. The thinking is The mechanism is the brain’s response to various stimuli. Mental activity is one that happens to everyone all the time . Thinking makes humans different from other animals. There are three Analysis of thinking. The basic Thinking, Intermediate And Analysis thinking. Thai language teachers in the 21st century have to very important to promote and develop thinking skills .The students towards higher-order thinking. Analytical Thinking, Solving problems Thinking, The Critical Thinking and Creativity Thinking. Thai language teachers will be taught how to model teaching, methods and techniques to the strategy is to develop thinking skills. In this essay, The writers for example teaching strategies :1) Bloom’s Taxonomy Model 2) Torrance’s Future Pro blem Solving Instructional Model 3) Synectics Instructional Model and 4) Phenphisut Nekmanuruk Instruction Model. Thai language teachers have to Event held at the teaching materials and equipment, As well as integrating thinking skills together. In order to develop higher-order thinking skills of students. This will enable the students to live happily in their daily work.